Fading challenges in Malay natural-dyed textiles: factors and conservation strategies - Syed Kamarulzaman, Sharifah Tahirah; Taif, Basitah; Ab Kadir, Muhammad Ismail; Abdul Razak, Rajabi (Nova Science Publishers, Inc., 2025)
Malay naturally-dyed textiles, particularly songket and limar songket, are significant cultural artefacts symbolising Malaysia’s rich heritage. These textiles, known for their intricate patterns and vibrant colours derived from natural dyes, are especially vulnerable to fading, a primary factor in their degradation. Prolonged exposure to light, especially ultraviolet (UV) radiation, accelerates the fading of these dyes, diminishing the aesthetic and cultural value of the textiles. This study focuses on the fading of natural dyes, identifying key factors such as light exposure, environmental conditions, and improper display practices that contribute to this degradation. It proposes conservation strategies, including light monitoring, controlled display environments, and proper storage techniques to mitigate fading. Case studies from the Department of Museums Malaysia (JMM) illustrate fading patterns and inform the recommended conservation practices. The outcomes underscore the need for a focused approach to address fading to ensure the protection and longevity of Malay naturally-dyed textiles for future generations.